Process-aware SSA-Conv-PatchTST for robust multi-horizon aeration-demand forecasting in full-scale wastewater treatment plants - Ran Song; Xiaole Mei; Xinhua Jiang; Xuelei Ma; Muqier Wudan; Wenlong Bai; Hao Lin; Zhi Li; Shengbin Gao (Journal of Water Process Engineering, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Role and therapeutic potential of icariin in metabolic diseases - Anni Song; Ran Wei; Yang Yang; Haoshuang Li; Fengyi Chen; Yutong Pang; Xiaotong Ma; Shijie Hao (Inflammopharmacology, 2026)

Unlocking the effects of cold plasma on enhancing the stabilization of oat flour: Insights from storage characteristics, lipidomics, and flavor analysis - Shunzhang Ma; Hao Ran; Jinquan Lin; Yuanlin Sun; Lizhen Zhang; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Stored Products Research, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Embryonic Proto-Tethys Ocean: Evidence from the early Ediacaran Kuyake ophiolite mélange along the Altyn Tagh in NW China - Hong-Ran Wang; Chuan-Lin Zhang; Hua-Dong Ma; Yan Jing; Masumeh Sargazi; Zhi-Hao Song (Precambrian Research, 2026)

A comprehensive review of emerging protein modification methods: modified properties and potential applications - Hao Zhu; Kaifang Guan; Xiaolin Liu; Ran Xiao; Ying Ma; Weihong Lu; Xue Han; Rongchu Wang; Tianjiao Niu (Food Chemistry, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Low N Deposition Coupled With Climate Warming Promote Soil Asymbiotic N Fixation via Increasing Microbial Specialists in Alpine Grassland - Ke Zhang; Yaoming Li; Ran Zhang; Anna Du; Zuyan Ma; Hang Shi; Juejie Yang; Wenli Ding; Hao Shen; Richard D. Bardgett; Huaiying Yao; Shikui Dong (Global Change Biology, 2026)
Biological nitrogen fixation (BNF) is a vital process for introducing new N into natural ecosystems, and this process has been demonstrated to be suppressed by high N deposition. However, the net ecological effect and underlying mechanisms of BNF under chronic low‐level N deposition, characteristic of terrestrial ecosystems, remain highly uncertain. Given that climate warming is a key environmental change factor concurrent with N deposition, it is important to investigate whether climate warming can change BNF activity and alter the effects of N deposition on BNF. To fill these knowledge gaps, we implemented a decade‐long‐term manipulation experiment in an alpine grassland ecosystem with 5 treatments, that is, experimental warming (W), low‐level N deposition (N L ), high‐level N deposition (N H ), combination of climate warming and low‐level N deposition (WN L ) and the control (CK). BNF rate was measured by 15 N 2 isotope discrimination. We found that N L significantly stimulated BNF by 112%, contrasting sharply with the complete suppression under N H . Climate warming alone increased the BNF rate by 123%, while the WN L amplified this effect, stimulating BNF by 234%. Structural equation modeling revealed that WN L selectively favored specific diazotrophic groups ( Desulfovibrio ), whose proliferation directly drove the observed BNF shifts. In this N‐limited alpine grassland, low‐level chronic N deposition, especially when combined with warming, fundamentally shifts the diazotrophic community structure by driving a process of niche contraction. This selection process functionally enriches specialized diazotrophs, resulting in a dramatic, positive feedback that significantly promotes the overall biological nitrogen input. Our findings highlight the potential for increased N inputs under realistic future climate scenarios and provide a scientific basis for precision N management in alpine grasslands, both on the Qinghai‐Tibetan Plateau and worldwide.

Effects of chronic social defeat stress on behavior and cognition by activating the ERS-NLRP3 signaling pathway in adult mice - XiaoLei Gao; Ran Hao; ZengYun Jing; GuangBiao Huang; Lina Wang; Anna Ma; ZhaoHui Zhang; Tong Zhao (Metabolic Brain Disease, 2025)

Regulation of phytoplankton community by mesoscale eddies and the East Indian Coastal Current in the southwestern Bay of Bengal during the northeast monsoon - Hao Chen; Yuanli Zhu; Lihua Ran; Mengjia Zhang; Xiao Ma; Hongliang Li; Feng Zhou; W.N.C. Priyadarshani; Zhibing Jiang (Marine Environmental Research, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

Grazing mediates soil nutrient stocks through changing the plant functional composition and plant biomass allocation in alpine grassland - Fengcai He; Shikui Dong; Chunhui Ma; Xinghai Hao; Hao Shen; Juejie Yang; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Data-driven differentiable model for dynamic prediction and control in wastewater treatment - Yun-Peng Song; Wen-Zhe Wang; Yu-Qi Wang; Wan-Xin Yin; Jia-Ji Chen; Hao-Ran Xu; Hao-Yi Cheng; Fang Ma; Han-Tao Wang; Ai-Jie Wang; Hong-Cheng Wang (Water Research, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Rotational grazing can enhance the soil available nutrients rather than plant diversity to promote ANPP of alpine steppe - Fengcai He; Shikui Dong; Juejie Yang; Xinghai Hao; Chunhui Ma; Hao Shen; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Transfer of pesticides and metabolites in corn: Production, processing, and livestock dietary burden - Fengjiao Hao; Xiaoqing Wang; Feixiang Ma; Ran Wang; Fengshou Dong; Xinglu Pan; Xiaohu Wu; Yongquan Zheng; Jun Xu (Science of The Total Environment, 2024)

Solvation structure manipulation of ester-based electrolyte by acetonitrile additive enables high-capacity and stable K-storage for phenazine-based anode - Xiaokang Chu; Ran Chen; Hang Chen; Hao Wang; Luanjie Nie; Haobo Xia; Qingxue Lai; Zixia Lin; Mengtao Ma; Hao Gong; Jing Zheng (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Effects of Tetraselmis subcordiformis (Wille) Butcher with antimicrobial peptides as feed additives on gut microbial community and immunity of turbot (Scophthalmus maximus L.) - Bingkui Zhu; Fengjie Sun; Zhengquan Gao; Ting Yao; Subing Han; Hao Zhang; Yuyang Ma; Yuyong Wu; Ran Du; Chunxiao Meng; Yulin Cui (Journal of Applied Phycology, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

A self-assembled 3D nanoflowers based nano-ELISA platform for the sensitive detection of pyridaben - He Chen; Li An; Meng Li; Hao Liu; Zhong Jin; Huan Ma; Jingwei Ma; Juan Zhou; Ran Duan; Di Zhang; Xiu Cao; Tieliang Wang; et al. (Food Chemistry, 2024)

Unravelling solvation structure and interfacial mechanism of pyrrolidinium-based ionic liquid electrolytes in potassium-ion batteries - Xiaokang Chu; Hao Wang; Chi Hu; Qingxue Lai; Luanjie Nie; Hang Chen; Ran Chen; Zixia Lin; Mengtao Ma; Jing Zheng (Chemical Engineering Journal, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Exploration of risk analysis and elimination methods for a Cr(VI)-removal recombinant strain through a biosafety assessment in mice - Wanting You; Qiuying An; Dongbei Guo; Zebo Huang; Lulu Guo; Zigui Chen; Hao Xu; Guangshun Wang; Yeting Weng; Zhangye Ma; Xiaoxuan Chen; Feng Hong; et al. (Science of The Total Environment, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Mapping cropland suitability in China using optimized MaxEnt model - Xiaoliang Li; Kening Wu; Shiheng Hao; Zhang Yue; Zhao Ran; Jinliang Ma (Field Crops Research, 2023)

Mapping of suitable habitats for earthworms in China - Xiaoliang Li; Kening Wu; Shiheng Hao; Long Kang; Jinliang Ma; Ran Zhao; Yue Zhang (Soil Biology and Biochemistry, 2023)

Potential effects of Ag ion on the host by changing the structure of its gut microbiota - Xin-Lei Wang; Nanyang Yu; Ying-Xue Ma; Hao-Ran Zhou; Chuan Wang; Si Wei; Ai-Jun Miao (Journal of Hazardous Materials, 2023)

Nitrogen fertilizer alleviates rice yield loss without increasing global warming potential under elevated temperatures - Yingying Shen; Kailu Wang; Yufei Zhao; Liqing Yang; Wenzhe Liu; Tongyang Yin; Xueqin Wang; Xuan Ran; Hao Guo; Yuru Ma; Xinying Wu; Yao Chen; et al. (Field Crops Research, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Strengthening ion uptake and mitigating volume change via bimetallic telluride heterojunction for ultrastable K-ion hybrid capacitors - Zhihan Zeng; Wenqi Zhang; Hao Ma; Yuyang Yi; Xueyu Lian; Xianzhong Yang; Ran Cai; Wen Zhao; Jingyu Sun (Chemical Engineering Journal, 2023)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

Innovative health risk assessments of heavy metals based on bioaccessibility due to the consumption of traditional animal medicines - Tian-Tian Zuo; Hao-Ran Qu; Hong-Yu Jin; Lei Zhang; Fei-Ya Luo; Kun-Zi Yu; Fei Gao; Qi Wang; Lei Sun; Huai-Zhen He; Shuang-Cheng Ma (Environmental Science and Pollution Research, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Biochemical characterization of caffeoyl coenzyme A 3-O-methyltransferase from wheat - Qing-Hu Ma; Hao-Ran Luo (Planta, 2015)

A two-dimensional electrophoresis reference map of human ovary - Lei Wang; Ye-Fei Zhu; Xue-Jiang Guo; Ran Huo; Xiang Ma; Min Lin; Zuo-Min Zhou; Jia-Hao Sha (Journal of Molecular Medicine, 2005)

Differential expression of glucose-regulated protein 78 during spermatogenesis - Ran Huo; Ye-fei Zhu; Xiang Ma; Min Lin; Zuo-min Zhou; Jia-hao Sha (Cell and Tissue Research, 2004)